(untitled) (Medico Legal Update, 2020)
Aim: This study aimed to determine the impact of mass media upon juvenile delinquency in Basra Central Prison and AL- Maqal Police Station Subjects and Methods: A descriptive analytic study design was carried out at juvenile delinquency in Basra Central Prison and AL- Maqal Police Station from 3rd February 2019 until 4th April 2019 in AL-Maqal Police Station and 14th April 2019 until 14th May 2019 in Basra Central Prison. Non – probability (purposive) sample of 100 juveniles who were Basra Central Prison and AL- Maqal Police Station were selected. To know the impact of mass media upon juvenile delinquency using several measures are Content-based Media Exposure Scale (C-ME), International Self-Report Delinquency Questionnaire (ISRD), and Subtypes of Antisocial Behavior questionnaire (STAB) of 60 items of statements that measure impact mass media on juvenile’s behavior; and these statements are loaded into seven dimensions including social; psychological; ethical; political; economic; religious; and violent. Reliability of instrument was determined through the use of Alpha Cronbach approach and the instrument validity was determined through a panel of experts. The analysis of the data was used descriptive statistics frequencies, percentages, mean, standard deviation and Analysis of Variance (ANOVA). In order to assess the impact of mass media upon juvenile delinquency. Results: The findings of the present study reveal that indicate to high percentage unsatisfactory behavior (44%) in social and psychological status, (53%) in violent status, while impact upon ethical, political, economic and religious unsatisfactory behaviors have low than third, the total percentage of unsatisfactory behavior of all sample as (28.3%). Conclusion: The study concluded that the unsatisfactory behavior level of (social, psychological, ethical, political, economic, religious, and violent) dimensions were moderate of juvenile delinquency.